Clinical comparison of fiber-reinforced composite and stainless steel wire for splinting periodontally treated mobile teeth - Aliye Akcalı; Pınar Gümüş; Mutlu Özcan (Brazilian Dental Science)
Objective: This clinical study evaluated the success of two different splint materials bonded on periodontally treated mobile teeth.